Overeducation among immigrants in Sweden: Incidence, wage effects and state-dependence - Pernilla Andersson Joona; Nabanita Datta Gupta; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2012)
The utilization and reward of the human capital of immigrants in the labor market of the host country has been studied extensively. In the Swedish context this question is of great policy relevance due to the high levels of refugee migration and inflow of tied movers. Using Swedish register data covering the period 2001-2008, we analyze the incidence and wage effects of overeducation among non-Western immigrants. We also analyze whether there is state-dependence in overeducation and extend the immigrant educational mismatch literature by investigating whether this is a more severe problem among immigrants than among natives. In line with previous research we find that the incidence of overeducation is higher among immigrants and the return to overeducation is lower indicating that immigrants lose more from being overeducated. We find a high degree of state-dependence in overeducation both among natives and immigrants, but to a higher extent among immigrants.
Keywords: J61; I21; J24; J31; F22; 330; educational mismatch; immigrants; wages; state-dependence; Migranten; Unterbeschäftigung; Bildungsertrag; Hysteresis; Vergleich; Bevölkerung; Schweden